THEORETICAL BASIS AND PRACTICAL APPLICATION OF THE SEIDEL METHOD : ITERATIVE APPROACH TO SOLVING LINEAR SYSTEMS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In the article Seidel method , that is linear one step first orderly iterative of themethod essence , application and approach conditions surrounding illuminated . Seidel method simple iteration from the method different aspects , in particular , iteration in the process initial from rapprochements come out consecutively calculation scheme The method is explained . approach condition theorem in the form of brought , its proof matrices and their typical numbers based on done increased . Seidel method approach for matrix typical by the modulus of numbers suddenly small to be necessity It is also emphasized that simple iteration method with in comparison Seidel method advantages and disadvantages , conditions compliance when done faster approach theorem and examples through is based on . Article in the end practical example brought , Seidel 5 rooms of the method in accuracy solution find process table in the form of shown . This article linear algebra and iterative methods in the field research take visitors for important source become service does .